Construction of a pergola and flower garden as a selfie spot for prospective new tourist destination bukit mahoni, Bangun Rejo, Kutai Kartanegara - Hatta Musthafa Adham Putra; Zakiah Hidayati; Anna Rulia; Eman Sukmana (Universitas Muhammadiyah Magelang, 2022)
Bukit Mahoni is located in Bangun Rejo Village, becoming a candidate for a new tourist destination in Kutai Kartanegara Regency. Capitalizing on the natural potential in the form of a hill overgrown with Mahogany trees, it is encouraging for the local Tourism Awareness Group (Pokdarwis) to be promoted as a new tourist spot. This program was carried out in collaboration with the Pokdarwis Mentari Bangun Rejo with the aim of providing support for the readiness of new tourism objects in Bangun Rejo. All activities are carried out by accommodating the needs of tourism infrastructure so as to build appropriate outputs, namely Pergola and Flower Garden. Through this Community Service it is hoped that residents can utilize, maintain and care for the facilities that have been builded.